Outcome of Kidney Transplantations Performed With Preformed Donor‐Specific Antibodies of Unknown Etiology. Issue 1 (13th November 2013) - Sicard, A.; Amrouche, L.; Suberbielle, C.; Carmagnat, M.; Candon, S.; Thervet, E.; Delahousse, M.; Legendre, C.; Chatenoud, L.; Snanoudj, R.
Abstract The detection of preformed donor‐specific alloantibodies (DSA) with multiplex‐bead arrays has led to the common observation that individuals without a history of pregnancy, transfusion or transplantation can have circulating anti‐HLA antibodies of unknown etiology. We retrospectively analyzed the risk of antibody‐mediated rejection (AMR) and graft outcome in 41 kidney transplant recipients with DSA of unknown etiology (DSA cause‐unk) at the time of transplantation. Twenty‐one patients received a posttransplantation desensitization protocol, and 20 received standard immunosuppressive therapy. The mean number of DSA was 1.4 ± 0.8, ranging from 1 to 5. Complement‐dependent cytotoxicity crossmatches were negative for all the patients. Flow cytometry crossmatches were positive in 47.6% of cases. The incidence of acute AMR was 14.6% at 1 year, regardless of the immunosuppressive regimen. No patients experienced graft loss following AMR. At month 12, across the entire population of patients with DSA cause‐unk, the outcomes were favorable: the measured glomerular filtration rate was 63.8 ± 16.4 mL/min/1.73 m2, the screening biopsies showed low frequencies of microvascular inflammation and no transplant glomerulopathy, and graft and patient survival were 100%. In conclusion, patients with DSA cause‐unk are able to mount AMR but have favorable 1‐year outcomes.